Dampak Pandemi Covid-19 terhadap Konsumsi Masyarakat Provinsi Jawa Barat - Tunnafisah, Latifa; Istiqomah, Istiqomah; Bambang, Bambang (Lingka Ekonomika, 2022)
The purpose of this study was to analyze (1) differences in food and non-food consumption before and during the Covid-19 pandemic, (2) differences in food and non-food consumption in rural areas before and during the Covid-19 pandemic, and (3) differences in food and non-food consumption in urban areas before and during the Covid-19 pandemic in West Java Province. This study used data analysis using the normality test, paired sample t-test and nonparametric tests using the Wilcoxon sign rank test. The results showed that: (1) there were differences in food consumption before and during the Covid-19 pandemic in West Java Province, (2) there were differences in non-food consumption before and during the Covid-19 pandemic in West Java Province, (3) there were differences in consumption food and non-food in rural areas before and during the Covid-19 pandemic in West Java Province, (4) there are differences in food consumption in urban areas before and during the Covid-19 pandemic, and there are no differences in non-food consumption in urban areas before and during the Covid-19 pandemic in West Java Province.